2014
DOI: 10.7727/wimj.2013.270
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to Pegylated Liposomal Doxorubicin: A Case Report

Abstract: On physical examination, her temperature was 98°F, pulse 83/minute, respiratory rate 18/minute, blood pressure 122/55 mmHg; oxygen saturation was 93% on room air and her weight was 130 lbs. Systemic examination revealed tremors that were related to parkinsonism. Laboratory data showed normal blood counts and normal liver and renal function. The patient was prescribed single agent chemotherapy with liposomal doxorubicin at the dose of 50 mg/m 2 every four weeks.Prior to the administration of the first dose of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…A representative example is Doxil®, which is a formulation of DXR encapsulated in PEGylated liposomes with several clinical approvals [19,79]. The use of Doxil® has been implicated in acute infusion reactions in up to 45% of the cancer patients who receive the drug without premedication with steroids and antihistamines, while 4-7.1% in pre-medicated patients [80][81][82]. A number of studies have confirmed the crucial role of complement activation in the onset of the HSRs [12,21,83].…”
Section: Complement Activation-related Pseudoallergy (Carpa)mentioning
confidence: 99%
“…A representative example is Doxil®, which is a formulation of DXR encapsulated in PEGylated liposomes with several clinical approvals [19,79]. The use of Doxil® has been implicated in acute infusion reactions in up to 45% of the cancer patients who receive the drug without premedication with steroids and antihistamines, while 4-7.1% in pre-medicated patients [80][81][82]. A number of studies have confirmed the crucial role of complement activation in the onset of the HSRs [12,21,83].…”
Section: Complement Activation-related Pseudoallergy (Carpa)mentioning
confidence: 99%
“…The severity of CARPA after systemic liposomal administration in patients is influenced by morphological properties, size, surface charge, PEGylation, and cholesterol content, amongst other characteristics of liposomes [268]. A representative example is Doxil Ò , which has been reported to elicit rare but serious acute infusion reactions in cancer patients [269]. Therefore, CARPA has been recognized as a safety issue.…”
Section: Complement Activation-related Pseudoallergy (Carpa) Upon Nan...mentioning
confidence: 99%
“…LPS, the most widely used lipid nanomaterial is associated with a serious toxic effect—an anaphylactic shock. This incidence was considerably high with conventional LPS; however, the PEGylated LPS have reduced the chances [ 280 , 281 ]. The damaging impact of SLNs over the biological system usually depends upon the ingredient i.e.…”
Section: Loopholes In Designed Nano-ddsmentioning
confidence: 99%